2016
DOI: 10.1016/j.jclinepi.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

A third of systematic reviews changed or did not specify the primary outcome: a PROSPERO register study

Abstract: We recommend review authors carefully consider primary outcome selection, and journals are encouraged to focus acceptance on registered systematic reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 12 publications
4
54
0
Order By: Relevance
“…A recent study compared 80 non-Cochrane systematic reviews with their published protocols, and found that almost all (92.5%) differed from their protocols in at least one of the methods-related “Preferred reporting items for systematic review and meta-analysis protocols” (PRISMA-P) items and their subcategories, with only 7% of these providing an explanation [14]. Similar discrepancies between non-Cochrane systematic reviews and their PROSPERO protocols have been reported [1518]. Although these discrepancies appear to be fairly common, reasons for the differences are rarely addressed.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study compared 80 non-Cochrane systematic reviews with their published protocols, and found that almost all (92.5%) differed from their protocols in at least one of the methods-related “Preferred reporting items for systematic review and meta-analysis protocols” (PRISMA-P) items and their subcategories, with only 7% of these providing an explanation [14]. Similar discrepancies between non-Cochrane systematic reviews and their PROSPERO protocols have been reported [1518]. Although these discrepancies appear to be fairly common, reasons for the differences are rarely addressed.…”
Section: Discussionmentioning
confidence: 71%
“…64% of reviews (n=25) exhibited changes in the "outcome" section. When authors make post-protocol modifications to review outcomes (that is, addition, removal, or re-prioritization) based on significance of outcome in the completed review, it can introduce bias into the review process, mislead readers and possibly affect patient care [60][61][62][63][64][65]. Moreover, through awareness of all study characteristics, systematic reviewers might be able to drive the results in different ways regarding participants (e.g., by applying age limits or rules when not all patients in a study met the inclusion criteria), intervention and comparison (e.g., omission of comparators which show an intervention less effective than the retained comparators), and definition of study designs (e.g., broadening of the types of studies included beyond randomized controlled trials alone to other potentially less-robust forms of comparison).…”
Section: The Categories and Impact Of Changesmentioning
confidence: 99%
“…(PRISMA-P) items and their subcategories, while a mere 7% provided an explanation [67]. Additionally, an existing study investigated difference between non-Cochrane systematic reviews and their PROSPERO records and found that a third of systematic reviews changed or did not specify the primary outcome [63]. The existing researches showed that the differences between the published non-Cochrane reviews and their protocols were quite common.…”
Section: Improving the Transparency And Its Implementationmentioning
confidence: 99%
“…Journal editors and systematic reviewers therefore need to be mindful of whether the reported outcomes and exact analyses were selected prior to data analysis . Regrettably, it is not uncommon for even primary outcomes to change between study planning and completion, potentially undermining the integrity of the study . Reasons for, and timing of, any changes to planned reporting should be sought from trial authors.…”
Section: Declaration Of Interestmentioning
confidence: 99%